Social anxiety and interpretation bias: examining clinical and subclinical components in adolescents. Issue 3 (8th April 2017) - Loscalzo, Yura; Giannini, Marco; Miers, Anne C.
Abstract : Background: This study aimed to examine whether different components of interpretation bias are clinical or dimensional features of adolescent social anxiety. The study analyzed the components of this bias at a subclinical level of Social Anxiety Disorder (SAD) and compared these with a clinical sample of adolescents with SAD. Method: Adolescents in the age range 13–17 years participated. A group with SAD ( n  = 30) was compared with a group with subclinical SAD ( n  = 60), and a non‐socially anxious group ( n  = 95). Results: Negative interpretation bias for social situations was found to be a dimensional aspect of social anxiety. In contrast, belief in negative interpretations of social situations appears to be a clinical feature. Contrary to expectations, endorsement of positive interpretations did not differ between the three groups. Conclusions: The results suggest that a screening instrument based on negative interpretations of social situations could be useful to detect adolescents at‐risk of developing SAD. In a clinical setting, the belief in negative interpretations and the presence of the bias in nonsocial situations should also be considered.